(untitled) (American Journal of Islam and Society, 1997)
The emergence of the five independent and predominantly Muslim statesKazakhstan, Kyrgyzstan, Tajikistan. Turkmenistan, and Uzbekistan-in the aftermath of the collapse of the Soviet Union raises the issue of the role of Islam in their future development. Since Islam does not allow a separation of religion and politics, Islamic political panies have already been active, albeit with different intensity, in these countries. None of these countries has had a history of independence; for a long time, they were colonized (their most recent history of colonization goes back to the 1860s. when the Russians began to conquer and colonize the Central Asian villages) by czarist Russia, then from 1917 by the communist czars. Consequently, after independence their political elite (for the most part, former communists) remain substantially unfamiliar with the practice of democratic governance. As such, even after changing the names of communist parties in their respective countries, they essentially practice authoritarian policies in which little or no political pluralism is tolerated. Therefore. any evolution of democracy in these statei in the immediate or middle-range future is unlikely. However. Kazakhstan and Kyrgyzstan are two exceptions to this rule. Not coincidentally. both Kazakhstan and Kyrgyzstan top the list of ethnically pluralist states, and their economies are doing well compared to their Central Asian counterparts. However, this ethnic pluralism has not only polarized their populations along indigenous and Russian lines but also keeps their leaders from allowing any substantial role for lslamist parties. Uzbekistan. Turkmenistan, and Tajikistan have a lesser problem emanating from ethnic pluralism. However, the lion’s share of these countries’ problems stems from the acutely authoritarian nature of their leader hip, and, more imponant, their severe economic underdevelopment. One has to keep these variables in mind as one reads Mehrdad Haghayeghi’s book, Islam and Politics in Central Asia. Describing the presence of Islam in Central Asia, The author states that "the sedentary populations of the oasis enclaves and the tribal populations of the Steppe and the surrounding regions" were differently influenced by Islam. He goes on to observe: The enormous size and remoteness oft.he Steppe, the lack of adequate military manpower. the political instability at the heart of the Arab empire, and the absence of ...